2005
DOI: 10.1063/1.1839551
|View full text |Cite|
|
Sign up to set email alerts
|

Determining the geometry of strongly hydrogen-bonded silanols in a layered hydrous silicate by solid-state nuclear magnetic resonance

Abstract: High-resolution solid-state NMR spectroscopy is exploited to obtain structural constraints involving strongly hydrogen-bonded silanols in octosilicate, a prominent member of the layered hydrous sodium silicates. Proton-silicon cross-polarization dynamics reveals that octosilicate contains two types of Q(3) silicons present in hydrogen-bonded -Si-O-Hcdots, three dots, centeredO-Si- and -Si-O(-)-type sites which can only be distinguished by their different abilities to cross polarize and the different mobilities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…The general behavior is also very similar to that reported for the different Si sites in silica gel by Sindorf and Maciel (1980) and examined in detail by Klur et al (2000) who showed that the C P dynamics could be characterized as being in the "slow exchange regime." A similar situation was also found for layered silicates by Gardiennet et al (2005) and appears to be characteristic of Q 3 Si-OH based polarization transfer from the hydroxyl protons, providing further support for this interpretation. It is not possible to provide more specific structural information on these sites from the present experiments, but it is worthwhile noting that the degree of substitution at the Al1 site is substantial, the three resonances accounting for approximately 22-27% of the total intensity of the quantitatively reliable single pulse silicon spectrum (Fig.…”
Section: Nmr Experimentssupporting
confidence: 73%
“…The general behavior is also very similar to that reported for the different Si sites in silica gel by Sindorf and Maciel (1980) and examined in detail by Klur et al (2000) who showed that the C P dynamics could be characterized as being in the "slow exchange regime." A similar situation was also found for layered silicates by Gardiennet et al (2005) and appears to be characteristic of Q 3 Si-OH based polarization transfer from the hydroxyl protons, providing further support for this interpretation. It is not possible to provide more specific structural information on these sites from the present experiments, but it is worthwhile noting that the degree of substitution at the Al1 site is substantial, the three resonances accounting for approximately 22-27% of the total intensity of the quantitatively reliable single pulse silicon spectrum (Fig.…”
Section: Nmr Experimentssupporting
confidence: 73%
“…Solid-state NMR spectroscopy provides important structural information and constraints that open new opportunities for determining the structures of molecularly ordered silicate frameworks. In particular, solid-state 29 Si NMR yields: (i) the numbers and relative populations of distinct 29 Si sites in the structure; (ii) the chemical natures of such sites (e.g., the degree of condensation Q n of four-coordinate 29 Si moieties, where n represents the number of next-nearest-neighbor Si atoms that are covalently bonded via bridging oxygen atoms); (iii) 29 Si–O– 29 Si connectivities among the different resolved sites; , (iv) internuclear 29 Si–O– 29 Si distances; , and (v) additional local composition and bonding details derived from NMR interactions of 29 Si nuclei (e.g., chemical shift anisotropies , or scalar couplings , ), including with other nuclei potentially present, e.g., 17 O, 27 Al, or 23 Na . Such detailed information provides stringent local structural constraints that can subsequently be combined to determine framework topologies (i–iii), to construct model candidate structures in conjunction with the space groups and unit cell shapes and sizes obtained from XRD data (iv), , to probe the accuracy of different candidate structures, , and/or to refine these structures by comparing NMR interactions measured experimentally and calculated from first principles (v). , Complete structure determination, however, remains a major challenge in non-, semi-, or nanocrystalline solids, where XRD provides little or insufficient information.…”
Section: Introductionmentioning
confidence: 99%
“…The initial oscillations are characteristic of the largely coherent nature of the polarization transfer in spin systems with moderate proton–proton couplings. Consequently, the Fourier transform of the time dependence leads to dipolar spectra (Figure , right) featuring modified Pake doublets due to the oscillating heteronuclear polarization transfer, while proton spin-diffusion leads to an isolated central peak. ,, …”
Section: Resultsmentioning
confidence: 99%
“…The dipolar coupling constants D CH exp and D NH exp were extracted from the splittings multiplied by a factor of √2 to account for the n = −1 CP matching condition. Simulated build-up curves and corresponding dipolar spectra were obtained with the SPINEVOLUTION program for isolated pairs of spins (in red), while the fitting of the experimental build-up curves and corresponding dipolar spectra (in blue) were obtained using the exact analytical treatment for isolated pairs of spins that includes spin diffusion effects and implemented using the Scilab software.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation